Comparison of Olive Oils Derived from Certified Organic and Conventional Agricultural Methods - Dolgun, Oguz; Ozkan, Gulcan; Erbay, Buket (Asian Journal of Chemistry, 2010)
The objective of this study is to compare the fruit properties, quality parameters and chemical composition of Gemlik and Memecik olive oils derived from certified organic and conventional agricultural methods. Olive samples were hand picked at one stage of ripeness index (RIVI) based on the degree of skin and pulp pigmentation. Before extraction, the following fruit properties were measured on each olive sample: width of olive (cm), length of olive (cm), weight of olives (g), weight of stones (g), weight of pulp (g), pulp/stone ratio (g), moisture of olives (%) and the oil content (%) on dry weight basis by Soxhlet method. To execute the experiment, the olives (Gemlik and Memecik) were mechanically processed at industrial level in present oil mill by using three-phase continuous equipment. The organic and conventional oils were analytically tested to determine the differences in fatty acid composition and in the minor components (tocopherols and phenolics). Also the main quality parameters (free acidity, peroxide number, K232, chlorophyll pigments, carotenoids, photometric colour index) were compared. The results showed that there were no consistent differences between the overall properties according to comparison of cultivation types. Only oleic acids were the highest levels in both olive oils of Gemlik and Memecik cultivar grown with the type of organic production methods used in the present experiment.